The small molecule inhibitor BX-795 uncouples IL-2 production from inhibition of Th2 inflammation and induces CD4+ T cells resembling iTreg - Tauber, Peter A.; Kratzer, Bernhard; Schatzlmaier, Philipp; Smole, Ursula; Köhler, Cordula; Rausch, Lisa; Kranich, Jan; Trapin, Doris; Neunkirchner, Alina; Zabel, Maja; Jutz, Sabrina; Steinberger, Peter; et al. (Frontiers in Immunology, 2023)
Background: Treg cells have been shown to be an important part of immune-homeostasis and IL-2 which is produced upon T cell receptor (TCR)-dependent activation of T lymphocytes has been demonstrated to critically participate in Treg development. Objective: To evaluate small molecule inhibitors (SMI) for the identification of novel IL-2/Treg enhancing compounds. Materials and Methods: We used TCR-dependent and allergen-specific cytokine secretion of human and mouse T cells, next generation messenger ribonucleic acid (mRNA) sequencing and two different models of allergic airway inflammation to examine lead SMI-compounds. Results: We show here that the reported 3-phosphoinositide dependent kinase-1 (PDK1) SMI BX-795 increased IL-2 in culture supernatants of Jurkat E6-1 T cells, human peripheral blood mononuclear cells (hPBMC) and allergen-specific mouse T cells upon TCR-dependent and allergen-specific stimulation while concomitantly inhibiting Th2 cytokine secretion. RNA-Seq revealed that the presence of BX-795 during allergen-specific activation of T cells induces a bona fide Treg cell type highly similar to iTreg but lacking Foxp3 expression. When applied in mugwort pollen and house dust mite extract-based models of airway inflammation, BX-795 significantly inhibited Th2 inflammation including expression of Th2 signature transcription factors and cytokines and influx into the lungs of type 2-associated inflammatory cells such as eosinophils. Conclusions: BX-795 potently uncouples IL-2 production from Th2 inflammation and induces Th-IL-2 cells, which highly resemble induced (i)Tregs. Thus, BX-795 may be a useful new compound for the treatment of allergic diseases.